PENERAPAN ALGORITMA C4.5 DALAM MEMPREDIKSI KETERLAMBATAN PEMBAYARAN UANG SEKOLAH MENGGUNAKAN PYTHON - Victor Saputra Ginting; Kusrini Kusrini; Emha Taufiq Luthfi (Universitas Asahan, 2020)
Abstract – Payment of school fees is an important factor in carrying out education because payment of school fees is one of the important obligations in getting an education. Research conducted by Muqorobin, 2019 with the research title